2007
DOI: 10.1523/jneurosci.4378-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol-4,5-Bisphosphate Regulates NMDA Receptor Activity through α-Actinin

Abstract: Phosphatidylinositol-4,5-bisphosphate (PIP 2 ) has been shown to regulate many ion channels, transporters, and other signaling proteins, but it is not known whether it also regulates neurotransmitter-gated channels. The NMDA receptors (NMDARs) are gated by glutamate and serve as a critical control point in synaptic function. Here we demonstrate that PIP 2 supports NMDAR activity. In Xenopus oocytes, overexpression of phospholipase C␥ (PLC␥) or preincubation with 10 M wortmannin markedly reduced NMDA currents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
63
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 72 publications
3
63
0
1
Order By: Relevance
“…In the first set of experiments, the authors showed that PLC-catalyzed PIP2 hydrolysis suppressed NMDA currents in oocytes [Michailidis et al (2007) …”
Section: Phosphatidylinositolmentioning
confidence: 99%
See 4 more Smart Citations
“…In the first set of experiments, the authors showed that PLC-catalyzed PIP2 hydrolysis suppressed NMDA currents in oocytes [Michailidis et al (2007) …”
Section: Phosphatidylinositolmentioning
confidence: 99%
“…One complication of this experiment is that hydrolysis of PIP2 leads to production of inositol trisphosphate and diacylglycerol, which mobilize intracellular Ca 2ϩ release. However, even after "dumping" most of the Ca 2ϩ from internal stores, NMDA receptor currents were still inhibited by PLC-coupled receptor stimulation [Michailidis et al (2007) The authors then identified sites on NMDA receptors responsible for "sensing" PIP2, consistent with ␣-actinin binding sites on NMDA receptors [Michailidis et al (2007), their Figs. 5 (http://www.…”
mentioning
confidence: 94%
See 3 more Smart Citations